Knowledge, Attitude, and Practices of Nursing Students on Disaster Preparedness - Hershey Snow G. Aurelio; Brent Jericho C. Bautista; Rosalia M. Casimiro; Niel Kishia R. Dichoso; Rocel A. Endaya; Shanaia Kaye V. Ignacio; Cheena Mallari (Proceedings Series on Health & Medical Sciences, 2021)
Nurses play a critical part in disaster response, and having nursing skills to be prepared for a disaster is essential and valuable. Healthcare workers must be explicitly trained to respond during catastrophe; thus, this study focused to determine the student nurse's knowledge, attitude, and practices on disaster preparedness as future care provider. This utilized a quantitative descriptive-correlational approach, total enumeration sampling, and used a four-part survey questionnaire. The result showed that most respondents were female, aged 18 to 22, and a resident of rural area. Nursing students have a sufficient understanding of disaster preparedness, including the importance of effective disaster planning and preparation, disaster warnings and indicators, and the appropriate responses to consider in the event of a disaster. The nursing students have a positive attitude toward disaster preparedness, particularly regarding their families' safety. Nursing students agree that they have sufficient disaster preparedness strategies, although they are not always mentally and physically prepared when a disaster occurs. Findings revealed that students' disaster preparedness knowledge and practices significantly correlate with their demographic profile; their social integration improve as they progress through the year levels. Based on the collected data, the nursing students' knowledge, attitude, and practices are satisfactory; however, there is still potential to expand and enhance disaster preparedness knowledge, attitude, and practices. Continuing education and training workshops to become proficient in disaster preparedness could help students improve knowledge, attitude, and practices, resulting in better management and preparation for potential disaster occurrences.